Kritik Budaya Moralitas Pendidikan Sekolah Prespektif Neil Postman dan Azyumardi Azra - Achmad As'ad Abd. Aziz; Ach. Nurholis Majid (Institut Agama Islam Negeri Palopo, 2022)
This paper contains the results of a study on cultural criticism of school education morality. The school is a complete and structured educational center. The school becomes one of the complete educational centers and structures. As a whole, schools require mutual involvement between teachers and students to achieve certain goals. The integrity of the role is then supported by a structured process, starting from planning, implementation, to the process of monitoring and evaluation. The purpose of this research is to find out the criticism of the moral culture of school education according to Neil Postman and Azyumardi Azra, and to find out the construct of the idea of a culture of morality in school education according to Neil Postman and Azyumardi Azra. This study uses a type of qualitative research literature (Library Research). The method used in this study uses an interpretive approach, the researcher tries to reveal and identify the culture of morality in school education according to the thoughts of Neil Postman and Azyumardi Azra, so that all ideas, and the work of Neil Postman and Azyumardi Azra regarding Morals can be known. Sources of data in this study using two sources, namely, primary data sources and secondary data sources. Therefore, the sources of data collected in this study are documents related to the thoughts of Neil Postman and Azyumardi Azra about school education. The results in this study are that, in criticizing the culture of morality, Postman discusses at least five important things, including: In criticizing morality culture, Postman discusses at least five important things, including: (first) Teachers do not appear as top figures, (second) Children are not given critical thinking space, (thirth) The reality of rapidly developing technology, (four) Schools are only limited to fulfilling profession. Azra's thoughts on morality culture explain how education can liberate humans from physical work that shackles human nature to develop. Azra becomes exposed to his cultural critique of morality into several parts. (first) The orientation of education on the formation of artisans, (second) Education takes place in a schooling system. (thirth) Rigid school formalism.